Faster detection of snake and spider phobia: revisited. Issue 5 (May 2020) - Polák, Jakub; Sedláčková, Kristýna; Landová, Eva; Frynta, Daniel
Abstract: Snake and spider phobia are one of the most prevalent anxiety disorders, yet quick and reliable measures are rather scarce. Recently, attempts have been made to shorten two widespread measures of snake and spider fear, the Snake Questionnaire (SNAQ) and Spider Questionnaire (SPQ). The new 12-item scales demonstrate very good psychometric qualities in terms of internal consistency and discriminatory power. Using the same approach on a bigger sample from another cultural background, we aimed to verify psychometric properties of the short scales. In total, 2 644 Czechs completed the SNAQ, 1 816 of which also completed the SPQ. The item response theory revealed that nine and seven items on the shorter SNAQ and SPQ, respectively, were identical with the Hungarian study. The 12-item scales show excellent reliability (α = 0.84 and 0.91) and highly correlate with scores on the full versions (r = 0.81 and 0.89) as well as with fear and disgust ratings of snake and spider images. Thus, despite slight discrepancies in the selected items, we confirm that the shorter SNAQ and SPQ keep considerable diagnostic strengths and can be used in the clinical practice as reliable, easy-to- administer, and fast screening tools for snake and spider phobia. Abstract : Psychology; Arachnophobia; Animal fear; Item response theory; Ophidiophobia.